2019
DOI: 10.1521/aeap.2019.31.6.567
|View full text |Cite
|
Sign up to set email alerts
|

¿Te Recurseas? Mapping, Enumerating, and Describing Male and Transwomen Sex Workers in Venue-Based and Virtual Spaces in Lima, Peru

Abstract: HIV disproportionately affects men who have sex with men and transwomen in Latin America. Globally, efforts to map, enumerate, and describe male and transwomen sex workers (MTSWs) are limited. We mapped and described venue- and non-venue–based MTSWs and enumerated venuebased MTSWs in Lima, Peru's capital. With venue-based MTSWs, we identified and described the venues, SWs, and clients and enumerated the SWs. With non-venue–based MTSWs, we described SW offerings and SWs. Male SWs (MSWs) are concentrated downtow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Older transgender women may have had less exposure or access to preventive testing, free anti-retroviral treatment, and informational and anti-stigma campaigns, which have become more common over time. In addition, though nearly half of respondents engage in sex work, putting them at increased risks for HIV, HIV-associated TB, and other STIs, 15 increasing age was associated with a decline in sex work. Older women may have a reduced HIV risk or perception of risk, leading them to test less frequently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older transgender women may have had less exposure or access to preventive testing, free anti-retroviral treatment, and informational and anti-stigma campaigns, which have become more common over time. In addition, though nearly half of respondents engage in sex work, putting them at increased risks for HIV, HIV-associated TB, and other STIs, 15 increasing age was associated with a decline in sex work. Older women may have a reduced HIV risk or perception of risk, leading them to test less frequently.…”
Section: Discussionmentioning
confidence: 99%
“…9 Transgender women are often forced to leave home after experiencing physical, sexual, and/or verbal violence and family rejection, 10 11 with many migrating to cities where they have few resources and support networks. 12 High prevalence of sex work, often one of the only livelihood options available, 13 14 is linked with risky behaviors 15 and increases risks for STIs and other infectious diseases. 16 13…”
Section: Introductionmentioning
confidence: 99%
“…Te SGM who perform sex work are potentially more exposed to infectious diseases. A study conducted in Lima, the capital of Peru, revealed that HIV prevalence is 4.5% among male sex workers, mostly bisexuals, and reaches 16.6% among transgender women, mostly homosexuals [11]. It is known that sex work increases the prevalence of chronic diseases and mental health problems [12,13]; however, in Peru, the available scientifc evidence is limited.…”
Section: Introductionmentioning
confidence: 99%
“…In the aftermath of iPrEx and numerous PrEP implementation challenges that followed, emerging research among Peruvian MSM and trans women has highlighted the existence of mistrust of international drug trials, foreign investigators and Peruvian institutional actors implementing the studies as obstacles to widespread PrEP acceptance and use [22]. Notably, PrEP was approved by the Peruvian FDA in 2017 and yet, there is no current integration within Peru's public health system and availability for trans women occurs primarily in the context of HIV biomedical prevention research [23,24]. In this paper, we used qualitative methodology to explore the mistrust and its impact on research participation as reported by trans women who participated in a PrEP adherence trial and those who refused involvement in the study (i.e.…”
Section: Introductionmentioning
confidence: 99%